NANOCARRIERS FOR THE TREATMENT OF HIV AND FUNGAL INFECTIONS - SHWETA MAPARI,; PANKAJ PATIL, (International Journal of Pharma and Bio Sciences, 2015)
Infectious diseases like AIDS, tuberculosis had been threat to the mankind and the treatment for such diseases over the years had made the pathogens resistant to the drug therapy. Advent of nanotechnology based drug delivery systems however, has changed the picture. Drug delivery using nanocarriers has proved its potential by drastically improving the treatment for infectious diseases. This review provides an overview of different types of nanocarriers such as liposomes, polymeric micelles, dendrimers, solid lipid nanoparticles, polymeric nanoparticles and case studies involving the use of these nanocarriers in treating HIV and fungal infections.